Peningkatan Kemampuan Siswa dalam Menyelesaikan Masalah Matematika dengan Pembelajaran Daring Asinkronus dan Sinkronus - mairing, jackson Pasini; Rezeki, Maulida; Aritonang, Henry; Lada, Elyasib Yunas; Langkis, Langkis (Edumatica : Jurnal Pendidikan Matematika, 2021)
Online learning during the Covid-19 pandemic experienced various obstacles, especially on quotas, internet signals, and unsatisfactory learning outcomes. This research was aimed to improve the ability of 7th grade junior high school students in solving mathematics problems through asynchronous and synchronous approaches using learning videos, student worksheets and mathematics problems. This research was classified as class action research. The research subjects were 14 of 7th grade students from a public junior high school located on the suburb of Palangka Raya city, Central Kalimantan in the 2021/2022 academic year. The research was carried out in two cycles where the stages of each cycle were planning, implementating, observing and reflecting. The research instruments were lesson plans, mathematics problems, student worksheets, videos, pre- quizzes and end-of-cycle tests. The results of first cycle showed that average of the students' score was 7,1 (scale of 0-16) which 5 of 14 students (35,7%) sgot score at least 2 (scale of 0-4) in each problem. At second cycle, average of the students' score was 10.4 and all students got score at least 2 in each problem. Thus, the online learning in this research was able to improve students' ability to solve mathematics problems.